2009
DOI: 10.1063/1.3174435
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic instability of ion acoustic mode in permeating plasmas

Abstract: In plasmas with electron drift (current) relative to static ions, the ion acoustic wave is subject to the kinetic instability which takes place if the directed electron speed exceeds the ion acoustic speed. The instability threshold becomes different in the case of one quasi-neutral electron-ion plasma propagating through another static quasineutral (target) plasma. The threshold velocity of the propagating plasma may be well below the ion acoustic speed of the static plasma. Such a current-less instability ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 18 publications
0
40
0
Order By: Relevance
“…For typical parameters at comet Halley, we find that both V dH and V de can drive the wave unstable; the KAW is thus driven unstable in a current-less plasma. Such an instability was found for the ion acoustic wave by Vranjes et al (2009).…”
mentioning
confidence: 61%
“…For typical parameters at comet Halley, we find that both V dH and V de can drive the wave unstable; the KAW is thus driven unstable in a current-less plasma. Such an instability was found for the ion acoustic wave by Vranjes et al (2009).…”
mentioning
confidence: 61%
“…The instability may require rather high values for the electron current. A lower instability threshold may be obtained in the case of two interpenetrating (permeating) plasmas, which implies a current-less instability [1]. This will be demonstrated in the example of the solar wind propagating through the cometary dusty plasma.…”
Section: Introductionmentioning
confidence: 93%
“…Within kinetic theory, in our recent papers, 9,[24][25][26] we have shown that a new kind of instability may develop in such systems. The instability discussed for longitudinal electrostatic perturbations is purely kinetic by nature and currentless (the latter meaning that the plasma contains no currents in the initial state).…”
Section: Introductionmentioning
confidence: 99%